ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI PEMBIAYAAN KPR SYARIAH (Studi Pada BTN Syariah Bekasi) - Nurul Aulia Robiatul Adawiyah; Arief Widyananto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
This study aims to determine what factors can affect the realization of Sharia KPR financing at BTN Syariah Bekasi. The variables used in this study consist of financing period, fixed margin and financing frequency. This research is quantitative in nature using a questionnaire as a data collection tool. The population in this study were all customers who carried out KPR Syariah financing at BTN Syariah Bekasi with a sample size of 100 customers. Sampling using probability sampling techniques. The data analysis technique used is the classic assumption test, multiple linear regression analysis, the coefficient of determination, the t test and the F test. While the data processing in this study used the SPSS 25 program. From the hypothesis test using the t test, it is found that the variable period of financing has a positive but insignificant effect, while the variable margin and frequency of financing have a positive and significant effect on the realization of Islamic mortgage financing Based on the F test (simultaneous), the results show that the variable period of financing, fixed margins and frequency of financing jointly affect the realization of Sharia KPR financing.